PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DIREKTORAT PENILAIAN ALAT KESEHATAN DAN PKRT - Friska Dianti Anisa; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
To determine the effect of competence and work discipline on employee performance in the Directorate of Medical Device Assessment and PKRT. Purpose this research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to respondents, all of whom are employees of the Directorate for the Assessment of Medical Devices and PKRT, while the research method uses simultaneous and partially linear regression analysis. The hypothesis states that competence and work discipline simultaneous have a positive effect on employee performance. The hypothesis that partially states that competence and work discipline affect employee performance in the Directorate of Medical Device Assessment and PKRT.